The Influence of Information Technology on Employee Responsiveness in The Telecommunications Sector, Airtel Southeast Nigeria - Kelechi Ugwu; Ebele Onwuka; Felix Okwedy; Uzoamaka Chris-Ejiogu (Publikasi Indonesia, 2023)
Purpose: The study investigated how information technology has impacted the responsiveness of the telecommunication industry, Airtel, South East, Nigeria Methodology/approach: The study used a correlational survey design, with copies of the questionnaire serving as the main data collection tool. A probability simple random sampling technique was used to distribute the survey face-to-face using a five-point Likert scale. The data was tested using correlation to analyze the relationship between the variables. Result/Findings: The result of research hypothesis one indicates that a unit rise in teleconferencing applications results in a 0.996 increase in employee responsiveness at a 5 % level of significance. The result of research hypothesis two revealed that a unit increase in internet applications results in a 0.865 increase in service quality at a 5 % level of significance. The researchers suggest businesses provide opportunities for their employees' ongoing education and training, so they can gain the most recent credentials and expertise in their field. Contribution: The study established a gap in the conceptual framework relating the variables of teleconferencing software, internet, and service quality. This current study aims to close the conceptual and geographic coverage gaps in the literature. Practical Implications: The outcome of this study would help policymakers push for investments in opportunities for lifelong learning and promote collaborations between businesses, governments, and educational institutions. Novelty: This study contributed to the body of knowledge by identifying gaps in the literature and geographic coverage. Keywords: Information Technology, Teleconferencing Application, Employee Responsiveness, Resource Based Theory, Pearson Correlation, Nigeria.